Implementasi Strategi Manajemen Pendidikan Berbasis Motivasi Kerja dan Kinerja Guru dalam Pengembangan SDM Pendidikan di SMP Multazam Semarang - Wati Setiawati; Fan Al Muttaqin; Rika Septiyani; Ngurah Ayu Nyoman Murniati (Jurnal Manajemen Pendidikan, 2026)
This study explores the implementation of an educational management strategy based on work motivation and teacher performance to develop educational human resources at SMP Multazam Semarang. The background of this research lies in the strategic role of human resource management (HRM) and school leadership in improving teacher professionalism, motivation, and performance, which ultimately shape educational quality. Using a descriptive qualitative case study approach, data were collected through semi-structured interviews with school leaders, foundation management, permanent and non-permanent teachers, as well as through classroom observations, school meetings, training activities, and document analysis. Data were analyzed using thematic analysis and validated through source and technique triangulation. The findings are expected to show: (1) the formulation and implementation of HRM strategies, including teacher recruitment, training, performance appraisal, and reward systems; (2) driving and inhibiting factors of teacher work motivation in a religious school climate; (3) manifestations of teacher performance in planning, implementing, and evaluating learning and school participation; and (4) the implications of these strategies for the development of educational human resources. The study concludes that structured and vision-aligned educational management, mediated by teacher work motivation, contributes positively to teacher performance and the systematic development of educational human resources at SMP Multazam.